The Influence of Waqf Distribution and Promotion on Community Trust (Case Study: Tabung Wakaf Indonesia) - Dina Yustisi Yurista; Mohammad Noviani Ardi (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2019)
Waqf is a potential source of funds to overcome social problems, but most poverty reduction programmes rely on foreign credit, especially from the World Bank. In this case, the development of a waqf by a nadzir can be an alternative source of funding in the general economic empowerment, which is supported by society’s trust in waqf institutions. Therefore, this study is conducted to identify the factors that determine public trust and to examine the influence of waqf distribution and promotion on society trust in waqf funds managed by Tabung Wakaf Indonesia. This paper used quantitative methods and utilized primary data through direct surveys with questionnaires were collected and analyzed using multiple regression analysis. The findings reveal that promotion and distribution have significant relationships with society trust. In addition, this study indicates that distribution has the greater impact than promotion on influencing society trust in waqf management. The findings nevertheless give a wide understanding of the concept of public trust and its antecedent in the context of Tabung Wakaf Indonesia.